Pengaruh Stres Kekeringan terhadap Pertumbuhan dan Kandungan Sinensetin Tanaman Kumis Kucing (Orthosiphon aristatus (Blume) Miq.) - Hadiyanti, Nugraheni; Muharram, Muhammad; Probojati, Rasyadan Taufiq (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
The response of plants to environmental stress depends on the type of plant, the level, and the duration of stress. Drought stress affects growth, development, and the content of secondary metabolites produced by the plant. Kumis kucing (Orthosiphon aristatus (Blume) Miq.) is one example of a tolerant plant to drought stress. A study was conducted to compare the effect of several drought stress levels on plant growth and its sinensetin content. For this purpose, the experiment was carried out in a greenhouse with a one-factor complete randomized design, namely the level of water availability. The treatment tested consisted of: 100; 50; 37.5; 25; 12.5 percent of field capacity. Data were analyzed using analysis of variance and further tested with the Duncan Multiple Range Test level of 5% on significant results. The High-Performance Liquid Chromatography method was employed to test the sinensetin content (in percentage). The results showed that low water availability (50-12.5% field capacity) harmed plant growth and negatively affected leaf, stem, and root dry weight. The reduction in growth was highly significant in plants with water availability of 12.5% of field capacity. In low water availability, the plant that experience drought stress produced greater sinensetin content (0.0133%). Increased sinensetin in drought stress condition is a biochemical and physiological response of plants to unfavourable conditions.